Ultrasonics and sonochemistry: Editors’ perspective - Sivakumar Manickam; Daria Camilla Boffito; Erico M.M. Flores; Jean-Marc Leveque; Rachel Pflieger; Bruno G. Pollet; Muthupandian Ashokkumar (Ultrasonics Sonochemistry, 2023)
Ultrasonic waves can induce physical and chemical changes in liquid media via acoustic cavitation. Various applications have benefitted from utilizing these effects, including but not limited to the synthesis of functional materials, emulsification, cleaning, and processing. Several books and review articles in the public domain cover both fundamental and applied aspects of ultrasonics and sonochemistry. The Editors of the Ultrasonics Sonochemistry journal possess diverse expertise in this field, from theoretical and experimental aspects of acoustic cavitation to materials synthesis, environmental remediation, and sonoprocessing. This article provides Editors’ perspectives on various aspects of ultrasonics and sonochemistry that may benefit students and early career researchers.